1993
DOI: 10.1002/j.1460-2075.1993.tb05938.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-inducible expression in endothelial cells of an I kappa B alpha-like gene is regulated by NF kappa B.

Abstract: The transient expression of many different genes is mediated by the inducible transcription factor p50‐p65 NF kappa B, which in turn is regulated by complex formation with its inhibitor I kappa B alpha. We describe here that in porcine aortic endothelial cells, either IL‐1 alpha, TNF alpha or LPS upregulates an inhibitor of NF kappa B which we refer to as ECI‐6. ECI‐6 is by structural and functional criteria an I kappa B alpha protein, the porcine homologue of MAD‐3, pp40 and RL/IF‐1. We have studied the promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
201
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(219 citation statements)
references
References 44 publications
16
201
2
Order By: Relevance
“…In the case of c-Rel and v-Rel proteins, it has been shown that a potential protein kinase A (PK-A) phosphorylation site localized close to the nuclear localization sequence (NLS) in the RHD is involved in regulating nuclear/cytoplasmic distribution (Mosialos et al, 1991 Our finding that the constitutive activation, at least to some extent, is due to a loss of regulation by IKB-a, also suggests a way of explaining how to escape the autoregulatory feedback loop. As the gene coding for IKB-a contains KB-motifs in its own promoter, a consequence of high constitutive levels of KB binding proteins should result in overexpression of IKB (de Martin et al, 1993;Le Bail et al, 1993;Scott et al, 1993;Sun et al, 1993). This in turn would down-regulate KB activity, unless a mechanism such as the one described here is implemented.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of c-Rel and v-Rel proteins, it has been shown that a potential protein kinase A (PK-A) phosphorylation site localized close to the nuclear localization sequence (NLS) in the RHD is involved in regulating nuclear/cytoplasmic distribution (Mosialos et al, 1991 Our finding that the constitutive activation, at least to some extent, is due to a loss of regulation by IKB-a, also suggests a way of explaining how to escape the autoregulatory feedback loop. As the gene coding for IKB-a contains KB-motifs in its own promoter, a consequence of high constitutive levels of KB binding proteins should result in overexpression of IKB (de Martin et al, 1993;Le Bail et al, 1993;Scott et al, 1993;Sun et al, 1993). This in turn would down-regulate KB activity, unless a mechanism such as the one described here is implemented.…”
Section: Discussionmentioning
confidence: 96%
“…Released NF-cKB/Rel complexes translocate to the nucleus and transactivate their respective target genes. One of the target genes encodes the IKB-a protein and this autoregulatory feedback loop is most probably responsible for the transient nature of the induction of this pathway (de Martin et al, 1993;Le Bail et al, 1993;Scott et al, 1993;Sun et al, 1993). The current theory for the constitutive lymphoid activity of the KB-motif invokes a constitutive activation of this pathway, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that treatments with IFN-␥ also did not appreciably alter the kinetics or degree of I B-␣ resynthesis. Because I B-␣ resynthesis is known to be positively regulated by NF-B activity [36,37], failure to affect this event suggested that the entire process of NF-B activation is not impeded by IFN-␥. Other experiments indicated that IL-4 and IL-10 also failed to affect LPS-induced I B-␣ degradation or I B-␣ resynthesis (data not shown).…”
Section: Nf-b Activity Is Required For Tsg-14 Induction But Is Unaffementioning
confidence: 99%
“…Porcine IkBa is strongly homologous to human IkBa (de Martin et al, 1993) and this adenoviral vector has previously been shown to inhibit activation of NF-kB in human cells (Liu et al, 2001). rAd.IkBa was a kind gift from Dr Ranier de Martin (Department of Vascular Biology and Thrombosis Research, University of Vienna, Austria).…”
Section: Adenovirus-driven Overexpression Of Ijbamentioning
confidence: 99%